Proceedings of the 19th International Ship and Offshore Structures Congress - Guedes Soares, Carlos; Garbatov, Y. e editor (CRC Press/Balkema, 2015)
This three-volume work presents the proceedings from the 19th International Ship and Offshore Structures Congress held in Cascais, Portugal on 7th to 10th September 2015. The International Ship and Offshore Structures Congress (ISSC) is a forum for the exchange of information by experts undertaking and applying marine structural research